Jesus, a popstar? Image and cinematographic representation of the Nazaren between 1905 and 1927 - Soares, Caroline da Silva; Furlani, João Carlos (Romanitas - Revista de Estudos Grecolatinos, 2013)
Review of: CHEVITARESE, André Leonardo. Jesus no cinema: um balanço histórico e cinematográfico entre 1905 e 1927. Rio de Janeiro: Kliné, 2013. 188 p. v. 1.
Keywords: Historical Jesus; Cinema; Image; Representation